Application of Next Generation Quality/Statistical Process Control and Expert-Led Case Review to Increase the Consistency of Diagnostic Rates in Precancerous Colorectal Polyps. Issue 3 (July 2021) - Bonert, Michael; Collins, Andrew; Xenodemetropoulos, Ted; Dmetrichuk, Jennifer M.; Al-Haddad, Sahar; Major, Pierre; Naqvi, Asghar
Abstract : Background: Prior work suggests high interrater variability in the pathologist diagnostic rate (PDR) of the precancerous polyp sessile serrated adenoma (SSA). Objectives: To improve the diagnostic consistency in the pathological evaluation of colorectal polyp specimens with diagnostic rate awareness, using funnel plots (FPs)/control charts (CCs), and a focused group case review. Methods: All colorectal polyp specimen (CRPS) reports September 2015 to August 2017 were analyzed at one institution. PDRs were extracted using a hierarchical free-text string matching algorithm and visualized using FPs, showing pathologist specimen volume versus PDR, and CCs, showing pathologist versus normed PDR. The FPs/CCs were centered on the group median diagnostic rate (GMDR). Pathologists were shown their baseline SSA diagnostic rate in relation to the practice, and in January 2017, there was a focused group case review/open discussion of approximately 40 sequential cases signed as SSA with a gastrointestinal pathology expert. Results: Nine pathologists interpreted more than 250 CRPSs per year. FPs/CCs for the first and second years showed 6/4 and 3/1 P < .05/ P < .001 pathologist outliers, respectively, in relation to the GMDR for SSA and 0/0 and 0/0 P < .05/ P < .001 pathologist outliers, respectively, in relation to the GMDR for tubular adenoma (TA). An in silico kappa (ISK) for SSA improved from 0.52 to 0.62. Conclusion: Diagnostic rate awareness facilitated by FPs/CCs coupled with focused expert-led reviews may help calibrate PDR. Variation in SSA PDRs still remains high in relation to TA. ISK represents an intuitive, useful metric and Next Generation Quality/Statistical Process Control a promising approach for objectively increasing diagnostic consistency. Abstract : Supplemental Digital Content is Available in the Text.